STRATEGI MARITIME SILK ROAD CHINA DAN PROSES SEKURITISASI KEAMANAN MARITIM FILIPINA (2018–2023) - Maisa, Raden; Enrizki, Darryl; Setiawan, Fajar Ajie (Universitas Prof. Dr. Moestopo (Beragama), 2024)
The Maritime Silk Road (MSR), as part of the Belt and Road Initiative (BRI), has become a key instrument for China to expand its influence in Southeast Asia, including the Philippines. Beyond being an economic project, MSR also serves as a maritime expansion strategy, where the development of ports and logistics infrastructure has dual-use potential, benefiting both economic and geopolitical interests. Securitization theory explains how this initiative strengthens China’s territorial claims in the South China Sea, supported by the presence of the China Coast Guard (CCG) and maritime militias, which employ gray zone tactics to exert control over disputed waters without direct military confrontation. The Regional Security Complex (RSC) theory illustrates how the Philippines' policy toward MSR has shifted under two different administrations. Rodrigo Duterte (2016–2022) adopted a more accommodative approach, accepting MSR investments to drive economic growth and infrastructure development, while Bongbong Marcos (2022–2023) took a firmer stance by reassessing the Philippines’ participation due to escalating CCG activities in disputed areas. MSR is not merely an economic initiative but also a securitization and geopolitical expansion tool for China, creating a dilemma for the Philippines between economic benefits and threats to its maritime sovereignty, with significant implications for regional security dynamics in Southeast Asia.